A Benzoquinone Imine Assisted Ring‐Opening/Ring‐Closing Strategy of the RCOCHN1N2 System: Dinitrogen Extrusion Reaction to Benzimidazoles1. Issue 19 (19th May 2017) - Kumar, Atul; Ahmed, Qazi Naveed
Abstract : A mild, three‐component dinitrogen extrusion reaction proceeding at room temperature to give different 1, 2‐disubstituted benzimidazoles from 2‐oxoaldehydes, 4‐azidophenol, and benzotriazoles was successfully developed. Mechanistically, this transformation occurs through the benzoquinone imine assisted ring opening/ring closing of a highly unstable RCOCHN 1 N 2 system. Abstract : A mild, three‐component dinitrogen extrusion reaction proceeding at room temperature to give different 1, 2‐benzimidazoles from 2‐oxoaldehydes, 4‐azidophenol, and benzotriazoles is successfully developed.